Sonographic Measurement of the Fetal Iliac Bone: Growth and Relation to Femur Length in Assessment of Gestational Age - Jaffe, Richard; Santolaya, Joaquim; Warsof, Steven L. (American Journal of Perinatology, 1993)
Diagnostic ultrasonography has given us the opportunity to diagnose several congenital malformations in utero. Skeletal dysplasias is a heterogeneous group of disorders of the skeleton. Although disorders of bone growth are often diagnosed in utero, it is usually a general diagnosis because the exact syndrome cannot be specified. This is due to the fact that many anomal ies of the skeleton have similar features. The wing of the iliac bone can be either affected or normal in skeletal dysplasias and its appearance may help in the differential diagnosis. This study was undertaken to establish values for the width of the iliac bone wing during normal gestations and thus enable us to use it in the evaluation of fetal growth and the recognition of specific congenital anomalies.